Characterization of the complete chloroplast genome of Musella lasiocarpa. Issue 2 (3rd July 2018) - Zhang, Lei; Guo, Xinyi; Wang, Zefu; Wang, Mingcheng; Hu, Quanjun
Abstract: The whole chloroplast (cp) genome sequence of Musella lasiocarpa has been characterized from Illumina pair-end sequencing. The complete cp genome was 169, 178 bp in length, containing a large single copy (LSC) region of 87, 884 bp and a small single copy (SSC) region of 11, 144 bp, which were separated by a pair of 35, 075 bp inverted repeat (IR) regions. The genome contained 138 genes, including 88 protein-coding genes (87 PCG species), 37 tRNA genes (30 tRNA species), and eight ribosomal RNA genes (four rRNA species). The most of gene species occur as a single copy, while 23 gene species occur in double copies. The overall AT content of M. lasiocarpa cp genome is 63.3%, while the corresponding values of the LSC, SSC, and IR regions are 64.9, 69.2, and 60.3%, respectively. The cp genome sequence is similar to that of the genus Musa.